Sistem Penerimaan Dan Pengeluaran Kas Dengan Metode Langsung Untuk Mempermudah Manajemen Keuangan Pada Perusahaan Food and Baverage - Arsito Ari Kuncoro; Zaenal Mustofa; Febryantahanuji Febryantahanuji (Pusat Riset dan Inovasi Nasional, 2023)
This information system discusses cash receipts and disbursements, this research was conducted at a company engaged in food and beverage (ice cream). The problem faced is the recording of cash receipts and disbursements which are still recorded in the books and then transferred to Microsoft Excel, so that the recording of cash receipts and disbursements cannot be properly archived per month or yearly. The method used by using the R&D development method, a multi-user network-based cash receipts and disbursement accounting information system is also very much needed in companies in making decisions in cash receipts and disbursements. Building this information system using the Visual Basic programming language with a MySQL database, this application is made to calculate cash receipts and disbursements reports using the direct method. With the existence of an inventory system, it is hoped that the company can assist in financial management in recording cash receipts and disbursements and the required reports.